Attitudes Towards Migrants during Crisis Times - Marisol Rodríguez Chatruc; Sandra V. Rozo (Institute of Labor Economics (IZA), 2021)
How are natives' attitudes towards migrants shaped by economic crises? Natives could show more empathy towards migrants as everyone faces a common threat. Alternatively, natives' prejudice could rise as competition for scarce economic opportunities increases. We conduct an online survey to 3,400 Colombian citizens and randomly prime half of them to think about the economic consequences of COVID-19, before eliciting their altruism and attitudes towards Venezuelan forced migrants. We find that natives' attitudes towards migrants are substantially more negative in the treatment relative to the control group. Individuals ages 18 to 25 years, however, respond by showing more altruism.
Keywords: D72; F2; O15; R23; 330; migration; COVID-19; attitudes; priming; altruism